A Critical Analysis of Loopholes in Branchless Banking in Pakistan - Rizvi, Syed Arshad Ali; Mahfooz, Izza; Ahmad, Wahab (Journal of Development and Social Sciences, 2024)
This study aimed to critically explore the loopholes in Branchless Banking in Pakistan. This study was qualitative, and a total of 16 cyber investigators were interviewed face-to-face from the district Faisalabad. Collected data were analyzed using the content analysis method. Results of this study are presented under different key themes, i.e. (i) serious violations of Know Your Customer (KYC) & Customer Due Diligence (CDD), (ii) BVS (Biometric Verification System) Failure followed by some sub-themes. This study unveiled that the security of internet-based financial services is a great concern. Whereas violations of KYC and CDD reflect various vulnerabilities that augment financial crimes. Ineffective use of biometric verification systems, poorly maintained retailer records, and the operation of unauthorized individuals aggravate the risks of financial crimes. There is a need for a real- time monitoring system of transactions, a strict BVS, and an awareness campaign for public on safe use of branchless banking.